2023
DOI: 10.3390/agronomy13020328
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Machine-Learned Regression Models to Estimate Internal Air Temperature and CO2 Concentration of a Pig House

Abstract: Carbon dioxide (CO2) emissions from the livestock industry are expected to increase. A response strategy for CO2 emission regulations is required for pig production as this industry comprises a large proportion of the livestock industry and it is projected that per capita pork consumption will rise. A CO2 emission response strategy can be established by accurately measuring the CO2 concentrations in pig facilities. Here, we compared and evaluated the performance of three different machine learning (ML) models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To evaluate the performance of these various algorithms [62][63][64][65], the authors used several metrics, including mean-squared error (MSE), root-mean-squared error (RMSE), mean absolute error (MAE), and R-squared (R 2 ) as…”
Section: Selection Of Best Suited Modelsmentioning
confidence: 99%
“…To evaluate the performance of these various algorithms [62][63][64][65], the authors used several metrics, including mean-squared error (MSE), root-mean-squared error (RMSE), mean absolute error (MAE), and R-squared (R 2 ) as…”
Section: Selection Of Best Suited Modelsmentioning
confidence: 99%
“…Research has been conducted on predicting CO 2 mass concentration based on traditional machine learning methods, and some results have been obtained in predicting CO 2 concentrations in pig houses [ 14 ], composting environments [ 15 ], and building construction environments [ 16 , 17 ], and with regard to urban carbon emissions [ 18 , 19 ], crop CO 2 emissions [ 20 ], and ambient air pollution [ 21 , 22 ]. Although these CO 2 mass concentration prediction models can express the trends of internal changes of CO 2 in the environment and achieve certain prediction results, they require large amounts of valid data as experimental support, which creates a large and tedious workload.…”
Section: Introductionmentioning
confidence: 99%
“…Korean scientists have assessed the impact of livestock farms on carbon dioxide emissions using machine learning models, including ElasticNet, RFR, and SVR. They found that the random forest model provides the best reproducibility of the experimental data [19].…”
Section: Introductionmentioning
confidence: 99%